Hubungan Frekuensi dan Durasi Menyusui dengan Kenaikan Berat Badan Bayi - Fitri Adriani; Erniawati Erniawati; Sumarni Sumarni; Ningsi Anggraeni; Lilis Suryani (Madu Jurnal Ilmu Kebidanan, 2026)
The infant period is a phase of rapid growth that requires optimal nutritional intake, with breast milk serving as the best source of nutrition. Successful breastfeeding practices, particularly breastfeeding frequency and duration, are considered important factors in supporting adequate nutritional intake and infant weight gain. This study aimed to analyze the association between breastfeeding frequency and duration and infant weight gain in the working area of Pabbentengan Public Health Center, Gowa Regency. This quantitative study employed a cross-sectional design. The sample consisted of 30 infants selected using a total sampling technique in the working area of Pabbentengan Public Health Center in 2025. Data were collected using questionnaires to assess breastfeeding frequency and duration, as well as observation sheets based on the Maternal and Child Health Handbook (KIA Book) to record infant weight gain. Data were analyzed using univariate and bivariate analyses with the One-Way ANOVA test. Most infants were female (53.3%) and aged 1 month (36.7%). The average infant weight gain was 0.69 kg. The majority of infants had a breastfeeding frequency of fewer than 8 times per day (63.3%) and a breastfeeding duration of 10–15 minutes (63.3%). The One-Way ANOVA test showed that there was no significant association between breastfeeding frequency and infant weight gain (p = 0.123), nor between breastfeeding duration and infant weight gain (p = 0.053). Breastfeeding frequency and duration were not significantly associated with infant weight gain in the working area of Pabbentengan Public Health Center.